Incidence and risk factors of loss to follow-up among HIV-infected children in an antiretroviral treatment program - Suttipong Kawilapat (2020)
© 2019 Kawilapat et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Introduction The success of antiretroviral treatment (ART) programs can be compromised by high rates of patient loss to follow-up (LTFU). We assessed the incidence and risk factors of LTFU in a large cohort of HIV-infected children receiving ART in Thailand. Methods All children participating in a multicenter cohort (NCT00433030) between 1999 and 2014 were included. The date of LTFU was 9 months after the last contact date. ART interruption was defined as ART discontinuation for more than 7 days followed by resumption of treatment. Baseline and time-dependent risk factors associated with LTFU were identified using Fine and Gray competing risk regression models with death or referral to another hospital as competing events. Results Of 873 children who were followed during a median of 8.6 years (interquartile range 4.5–10.6), 196 were LTFU, 73 died, and 195 referred. The cumulative incidence of LTFU was 2.9% at 1 year, 7.3% at 5 years and 22.2% at 10 years. Children aged 13 years and more had a 3-fold higher risk (95% confidence interval 2.06–4.78) of LTFU than those younger. Children who had interrupted ART within the previous year had a 2.5-fold higher risk (1.12–5.91) than those who had not. The risk of LTFU was lower in children stunted (height-forage Z-scores <-2 SD) (0.42–0.96) or underweight (weight-for-age Z-scores <-2 SD) (0.24–0.97). Conclusion Adolescence, ART interruption and absence of growth deficit were associated with LTFU. These may be warnings that should draw clinicians’ attention and possibly trigger specific interventions. Children with no significant growth retardation may also be at risk of LTFU.